2003
DOI: 10.1300/j017v21n03_02
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Substance Abuse Screening in Primary Care

Abstract: An automated screening system for substance abuse and mental health problems was developed and implemented in a rural primary care clinic. Eighty-nine patients were assessed with this system. The incidence of identified problems, 35% in total, was consistent with that found in previous studies of patients in general and medical settings. Additionally, over half of the patients assessed felt at least some need for mental health or substance abuse treatment. Nonetheless, because of the staff's concerns over pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Shoeneberger et al (2006), found alcohol to be the most common lifetime and current substance used in rural Kentucky, but with "unacceptable high levels" (p. 107) of illegal drug use. Screening patients in a rural primary care clinic, Hile (2003) found 35% of patients to have mental health and/or substance abuse problems that should be referred for treatment, consistent with rates in other settings. In addition, rural Americans face challenges in education, employment, all aspects of transportation, health, etc., (Ginsberg, 2004) which, combined with poverty and economic hardships outlined previously, increase the risk of emotional, behavioral and substance abuse problems (Conger & Elder, 1994).…”
Section: Rural Mental Health Substance Abuse and Child Welfaresupporting
confidence: 63%
“…Shoeneberger et al (2006), found alcohol to be the most common lifetime and current substance used in rural Kentucky, but with "unacceptable high levels" (p. 107) of illegal drug use. Screening patients in a rural primary care clinic, Hile (2003) found 35% of patients to have mental health and/or substance abuse problems that should be referred for treatment, consistent with rates in other settings. In addition, rural Americans face challenges in education, employment, all aspects of transportation, health, etc., (Ginsberg, 2004) which, combined with poverty and economic hardships outlined previously, increase the risk of emotional, behavioral and substance abuse problems (Conger & Elder, 1994).…”
Section: Rural Mental Health Substance Abuse and Child Welfaresupporting
confidence: 63%